2019
DOI: 10.1155/2019/1417967
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Accuracy of Four Malaria Diagnostic Methods in a High Transmission Setting in Coastal Cameroon

Abstract: Background. Despite recommendation from the World Health Organization that all malaria suspected patients undergo a parasitological confirmation using rapid diagnostic test or light microscopy prior to treatment, health facilities in remote malaria endemic settings sometimes resort to presumptive diagnosis of malaria for clinical management for various reasons. Following observation of this practice, we undertook a cross-sectional study aimed at comparing presumptive diagnosis based on axillary temperature, SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
(32 reference statements)
2
16
2
Order By: Relevance
“…In comparison with the light microscopy test, it was observed that there was a significant difference (P < 0.05). This disagrees with the findings of Moyeh et al [51], who although used a SD Bioline RDT (a much higher sensitivity diagnostic test) discovered in comparison with microscopy that there was no significant difference between the two diagnostic methods. In spite essential limitations encountered in using light microscopy [55], the diagnostic sensitivity was still high when compared to that of OPTIMAL-IT* RDT.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In comparison with the light microscopy test, it was observed that there was a significant difference (P < 0.05). This disagrees with the findings of Moyeh et al [51], who although used a SD Bioline RDT (a much higher sensitivity diagnostic test) discovered in comparison with microscopy that there was no significant difference between the two diagnostic methods. In spite essential limitations encountered in using light microscopy [55], the diagnostic sensitivity was still high when compared to that of OPTIMAL-IT* RDT.…”
Section: Discussioncontrasting
confidence: 99%
“…The nested PCR was able to detect only Plasmodium falciparum infection in the three (3) samples that appeared positive by the PCR. This agrees with the findings of Moyeh et al [51]; Bigoga et al [61]; Goselle et al [62] who all reported an economically viable number of Plasmodium falciparum when compared to Plasmodim ovale in Coastal Cameroun; Tiko and Plasmodium malariae in Nigeria respectively. But this is at variance with the findings of Fru-Cho et al [63] who reported substantial number of Plasmodium vivax in Coastal Cameroun and more number of Plasmodium malariae compared to Plasmodium ovale by Achonduh et al [64] in Bangolan.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Rapid diagnostic tests are vastly sensitive and specific compared with microscopy but also compare favourably with the polymerase chain reaction (PCR) [ 12 ], the most sensitive molecular technique for detecting parasites [ 13 ]. RDTs are limited mainly by their inability to detect infections at low parasitaemia.…”
Section: Introductionmentioning
confidence: 99%